Public acceptance of nuclear power among Malaysian students - Pauzi A.M.; Saad J.M.; Abu Bakar A.A.; Damahuri A.H.; Mohd Syukri N.S. (Institute of Physics Publishing, 2023)
Nuclear energy; Social networking (online); Electricity generation; Level of educations; Malaysian governments; Research methodologies; Research questions; Social networking sites; Sources of informations; Statistical packages; Nuclear fuels